Pengaruh Komposisi Azolla pinnata Pada Pakan Terhadap Pertumbuhan Ikan Bandeng (Chanos chanos Forsskal) di Balai Besar Perikanan Budidaya Air Payau (BBPBAP) Jepara - Wicaksono, Andy; Muhammad, Fuad; Hidayat, Jafron Wasiq; Suryanto, Damang (Bioma : Berkala Ilmiah Biologi, 2018)
Milkfish is one of the main commodities in the field of fishery and is known to be the most cultivated. One of the important’s factors to the success of milkfish cultivation is feed availability, both quality and quantity. Feed quality is an important aspect that must be fulfilled because of its relation to nutrients required for the fish growth. Azolla pinnata has a good potential that can be used as an additional ingredient for the fish growth because of its protein-rich content. This study is aimed to examine the effect of Azolla pinnata powder feed on growth of milkfish (length and body weight). This research was conducted in May – July 2017 at Aquatic Animal Health Management Laboratory, Center of Brackish Water Aquaculture of Jepara. The research design used is a Complete Randomized Design (CRD), using five treatments with different concentrations of Azolla pinnata powder, i.e. 0% as control, 10%, 20%, 30%, and 40%. Each treatments consist of three repeatitions. The parameters observed were milkfish growth (length and body weight) and dissolved oxygen (DO). Data were analyzed by Analysis of Variance (ANOVA) method. If the data showing significant differences it will be continued with Least Significance Different (LSD) test. The results showed that the administration of Azolla pinnata powder on the feed significantly influenced the growth (lenght and body weight) of milkfish. The most optimal and efficient feed composition for milkfish growth is done by feeding 40% of Azolla pinnata powder. The overall dissolved oxygen (DO) is still in suitable condition for the cultivation of milkfish. Key Words :  Azolla pinnata, dissolved oxygen, feed nutrition, milkfish